Magnetohydrodynamic turbulence - Biskamp, D. (Cambridge University Press, 2003)
This book presents an introduction to, and state-of-the-art account of, magnetohydrodynamic (MHD) turbulence. Applications to three topics from astrophysics are considered: the solar wind, accretion disks, and the interstellar medium. Suitable for graduate students and researchers working in turbulence theory, plasma physics and astrophysics.
Keywords: Magnetohydrodynamic instabilities.; Turbulence.; Instabilités magnétohydrodynamiques.; SCIENCE -- Physics -- Magnetism.; Magnetohydrodynamic instabilities; Turbulence